2019
DOI: 10.1590/0100-3984.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging and apparent diffusion coefficient values for evaluating terminal ileitis in patients with Crohn’s disease

Abstract: Objective: To determine the accuracy of diffusion-weighted imaging (DWI) in identifying terminal ileitis in patients with Crohn’s disease. Materials and Methods: This was a retrospective study of 38 consecutive patients with Crohn’s disease who underwent magnetic resonance enterography with DWI in a 3.0 T scanner. The patients were divided into two groups, on the basis of colonoscopy and biopsy findings: active inflammation; and inactive disease. Apparent diffusion coefficient (ADC) values were determined, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One recent study evaluated the use of diffusionweighted imaging in predicting the inflammatory activity of Crohn's disease in the distal ileum, showing that it presents good accuracy in the detection of an inflammatory process, in comparison with the identification of inflammation by colonoscopy, with a sensitivity and specificity of 88.8% and 95.0%, respectively, when a cut-off point of 2.1 × 10 −3 mm 2 /s for the ADC is applied (34) . Other studies have shown that diffusion-weighted imaging has the potential to substantially increase interobserver reproducibility in the evaluation of patients with Crohn's disease (35) , making it a useful tool in the monitoring of treatment responses in such patients (36,37) , as well as a good predictor of capsule retention during capsule endoscopy (38) .…”
Section: Grading the Inflammatory Activity Of Crohn's Diseasementioning
confidence: 99%
“…One recent study evaluated the use of diffusionweighted imaging in predicting the inflammatory activity of Crohn's disease in the distal ileum, showing that it presents good accuracy in the detection of an inflammatory process, in comparison with the identification of inflammation by colonoscopy, with a sensitivity and specificity of 88.8% and 95.0%, respectively, when a cut-off point of 2.1 × 10 −3 mm 2 /s for the ADC is applied (34) . Other studies have shown that diffusion-weighted imaging has the potential to substantially increase interobserver reproducibility in the evaluation of patients with Crohn's disease (35) , making it a useful tool in the monitoring of treatment responses in such patients (36,37) , as well as a good predictor of capsule retention during capsule endoscopy (38) .…”
Section: Grading the Inflammatory Activity Of Crohn's Diseasementioning
confidence: 99%
“…SR has better sensitivity. Durayski, 2019 [44] DWI and ADC histopathology terminal ileum active inflammation adult ADC: 88.8% Sens, 95% Spec DWI: 88.9%, 90% Spec ADC and DWI can accurately identify active inflammation in CD. Soydan, 2019 [68] combined DWI and T2w (SSFE, FIESTA), ADC ileocolonoscopy ileum and colon active inflammation adult ADC: 88.5% Sens, 57.1% Spec, 72.9% AUC DWI + T2 score: 88.4% Sens, 53.5 Spec.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is significant disagreement between studies regarding the optimal threshold value for ADC. The optimal ADC threshold for the maximum AUC ranged from 0.86 in one study [42] to as high as 2.1 in another study [44] . Nevertheless, the majority of studies included in our analysis proposed a threshold value of approximately 1.4, as summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Previously, only one study reported (again Lu et al) an ADC value of 1.6 on average in nonpathological intestine samples [34]. Two other studies, instead, reported values oscillating from 2 to 3 in healthy tissue [36,37]. An ADC lower than 2 was associated with inflammation in these studies and used as a cut-off to appraise inflammatory lesions.…”
Section: F Value and Adc In Healthy Tissuesmentioning
confidence: 98%